Surf tourism: segmentation by motivation and destination choice - Reis, Patrícia (2014)
The choice of touristic destinations depends on a number of factors, whether they’re personal, sociological or economical. The tourist demand is, thus, closely related to the decision that people make when planning their leisure activities. The following analysis seeks to provide information that will provide guidance to public authorities and companies planning in the strategy of sustainable tourism development within a specific segment, in this case surf tourism. This is a new business opportunity, currently having an assuming an important role in the development of regions. Motivation involves a selection process based also on the attributes of the destination. The main goal of this study, trying to make the characterization and profile of surf tourists, is the identification of factors implied on their motivation and the resulting segmentation of this market. The understanding of these issues constitutes is an important contribution for the promotion of a destination’s better performance and competitiveness. The study was based supported in a collection of data from a questionnaire to surf tourists. The market was segmented using multivariate analysis: factor and cluster analysis. The main results of this study have identified that surf tourists value certain attributes when choosing a destination for surfing, which can be synthesized in the factors "Destination", "Entertainment and Recreation" and " Surf Quality”, as well as and the existence of two opposing segments, that value different attributes, when choosing a surfing destination.